2015
DOI: 10.3109/14767058.2014.998647
|View full text |Cite
|
Sign up to set email alerts
|

Wound morbidity with staples compared with suture for cesarean skin closure by diabetic status

Abstract: The use of staples compared with subcuticular suture for cesarean skin closure is associated with increased wound morbidity. While this is true for non-diabetics, further studies of diabetics are needed to evaluate for a null or opposite effect of closure type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Although a number of studies have indicated that cosmetic outcome is similar between suture and staple closure [9][10][11]16,17], there is concern for use of traditional staples is the appearance of "train track" punctures if staples remain in longer than 4-7 days. In the general population this can be avoided by timely removal, however in patients with significant comorbidities, such as morbid obesity, a longer duration of staple retention is often necessitated to ensure wound closure [18,19]. The use of absorbable subcuticular staples eliminates the concern for early removal or longer retention needed pending the patient population and has been demonstrated to have similar cosmetic outcome to traditional closure techniques [5].…”
Section: Commentmentioning
confidence: 99%
“…Although a number of studies have indicated that cosmetic outcome is similar between suture and staple closure [9][10][11]16,17], there is concern for use of traditional staples is the appearance of "train track" punctures if staples remain in longer than 4-7 days. In the general population this can be avoided by timely removal, however in patients with significant comorbidities, such as morbid obesity, a longer duration of staple retention is often necessitated to ensure wound closure [18,19]. The use of absorbable subcuticular staples eliminates the concern for early removal or longer retention needed pending the patient population and has been demonstrated to have similar cosmetic outcome to traditional closure techniques [5].…”
Section: Commentmentioning
confidence: 99%
“…Sezaryen sonrası insizyon hattının stapler ya da subkütan sütürler ile kapatıldığı hastaların karşılaştırıldığı Fitzwater ve ark.nın çalışmasında; stapler uygulanan hastalarda YYE daha fazla olduğu belirtilmiştir. 9 Bununla beraber YYE gelişi-minde hastanın beslenmesi, vitamin ve eser element eksiklikleri, kullandığı ilaçlar, dokunun tipi ve özellikleri, hastanın genetik ve immünolo-jik kondisyonu gibi pek çok faktör yara iyileşmesi-nin hemostaz, inflamasyon, proliferasyon matürasyon ve remodelling safhalarını doğrudan etkileyerek bu süreci etkileyebilmektedir. 10 YYE gelişimini engellemek için çok farklı protokoller uygulanmakla birlikte, hastaların ne zaman banyo yapabileceği ile ilgili henüz bir fikir birliği sağlanmış değildir.…”
Section: Discussionunclassified
“…In these cases, we grouped the subsequent secondary analyses with their primary publication. For example, Fleisher et al 11 and Khalifeh et al 12 were included under Mackeen et al, 13 and Cooper et al, 14 Fitzwater et al, 15 and Subramaniam et al 16 were included under Figueroa et al 17…”
Section: Study Selectionmentioning
confidence: 99%